La construction d'une mémoire commune - Bérubé-Sasseville, Olivier (Les sépharades du Québec. Parcours d'exils nord-africains, 2017)
Keywords: Groupes populaires; Juifs; Maghrébins; Marocains

Famille et classe sociale: une approche systématique à la communication intrafamiliale - Chebat, Jean-Charles (Université de Montréal, 1976)
Keywords: Famille

Parenté et migration: le cas des Canadiens français à Montréal entre 1845 et 1875 - Gagnon, France (CHA / SHC, Historical Papers / Communications historiques, 1988)
Keywords: Famille

Modes de vie et modes de ville, activités et déplacements quotidiens à Montréal et Lyon - Ravalet, Emmanuel (Environnement Urbain / Urban Environment, 2007)
Keywords: Navettage

Les migrations quotidiennes de travail des actifs de la Petite Bourgogne - Brunet, Yves (Université de Montréal, 1971)
Keywords: Petite-Bourgogne; Quartiers

Les banlieues de l'immigration ou quand les immigrants refont les banlieues - Germain, Annick; Rose, Damaris; Richard, Myriam (Histoire de Montréal et de sa région, 2012)
Keywords: Banlieue; Italiens; Mile End; Mobilité résidentielle; Parc-Extension (quartier); Petite-Italie (quartier); Quartiers; Saint-Léonard

Metropolitan Expansion: The Challenge of Polycentricity - Sénécal, Gilles; Vachon, Nathalie (Montreal: The History of A North American City, 2018)
Keywords: Autoroutes; Banlieue; Centres commerciaux; Mobilité résidentielle; Métropole

Building and Reshaping the Suburban Landscape: The Role of Immigrant Communities - Germain, Annick; Rose, Damaris; Richard, Myriam (Montreal: The History of A North American City, 2018)
Keywords: Banlieue; Italiens; Mile End; Mobilité résidentielle; Parc-Extension (quartier); Petite-Italie (quartier); Quartiers; Saint-Léonard

Leonardo da Montreal: The Rhetoric of Italianità and the Canadian Post-Nation - Fratiloiu, Raluca Maria (Université Concordia, 2006)
Keywords: Centre Leonardo Da Vinci; Italiens

Reconstruction identitaire des jeunes en contexte migratoire: cas des jeunes québécois d'origine haïtienne - Craan, George-Marie (Université du Québec à Montréal, 2002)
Keywords: Haïtiens

Refugee Narratives in Montreal: Negotiating Everyday Social Exclusion and Inclusion - Manjikian, Lalai (Université McGill, 2014)
Keywords: Théâtre

Race and beauty in Canada: print culture, retail, and the transnational flow of products, images and ideologies, 1700s to present - Thompson, Cheryl (Université McGill, 2014)
Keywords: Esclaves; Noirs

Entrepreneurs in the New Economy: Immigration and Sex Effects in the Montreal Metropolitan Area - Paré, Sylvie; Therasme, Kelogue (Journal of International Entrepreneurship, 2010)
The recent literature on women’s entrepreneurship shows that they are underrepresented in the main stream economy when compared to their male counterparts, a phenomenon typically observed in other urban contexts. Approximately 30% of the entrepreneurs in the Montreal metropolitan area are women, active in a variety of sectors of the general economy. Their underrepresentation is still greater in the new economy, that is, those sectors that are knowledge-based and/or specialized in information technologies and communications. In this article, we examine the place of female entrepreneurs in the larger economy and in the new economy as related to their immigrant and/or ethnic origins. We seek in this paper to establish a comparative analysis of the situation of women entrepreneurs in immigrant-origin groups, focusing our attention on both the presence of women in entrepreneurial positions and the differential impact associated with membership in an immigrant-origin group. Based on data derived from Scott's Directory of 2007, we first determined an operational definition of the new economy and then analyzed the data from the perspective of sex and ethnic/immigrant origin. New economy enterprises represent approximately 12% of businesses in the Montreal metropolitan area, the majority of which are of the knowledge-based variety, and there is a relative, statistically significant absence of women from such enterprises. At the same time, there is a significantly greater presence of women drawn from minority groups, that is, from groups other than the Anglo-Canadian and French-Canadian dominant groups.
Keywords: Femmes; Travail